2017
DOI: 10.4103/0971-9784.197832
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of treatment of mitral stenosis on left atrium function

Abstract: Aim:Peak atrial longitudinal strain (PALS) is used to evaluate left atrium (LA) function in patients with mitral stenosis (MS), before and after percutaneous transmitral commissurotomy (PTMC) and mitral valve replacement (MVR).Methods:Patients with severe symptomatic MS, who were referred to our echocardiographic laboratory for a diagnostic examination before cardiac surgery or PTMC from October of 2014 to October of 2015, were included in the study.Result:The peak systolic global LA strain improved post-PTMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Though many studies have been done studying the impact of balloon mitral valvotomy on atrial volumes, atrial pumping function, and atrial reservoir functions [911], not many studies have studied the effect of valvotomy of global left atrial strain. Rohani et al studied the acute effect of balloon mitral valvotomy and mitral valve replacement in patients with mitral stenosis and concluded that the peak atrial longitudinal strain (PALS) was impaired in patients with severe symptomatic mitral stenosis and improved acutely after treatment [12]. Hemodynamic changes following BMV include decrease in left atrium afterload which is reflected by an increase in mitral valve area, decrease in diastolic transmitral gradients, and decrease in systolic pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies have been done studying the impact of balloon mitral valvotomy on atrial volumes, atrial pumping function, and atrial reservoir functions [911], not many studies have studied the effect of valvotomy of global left atrial strain. Rohani et al studied the acute effect of balloon mitral valvotomy and mitral valve replacement in patients with mitral stenosis and concluded that the peak atrial longitudinal strain (PALS) was impaired in patients with severe symptomatic mitral stenosis and improved acutely after treatment [12]. Hemodynamic changes following BMV include decrease in left atrium afterload which is reflected by an increase in mitral valve area, decrease in diastolic transmitral gradients, and decrease in systolic pulmonary artery pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Rohani et al [14] found that the peak systolic global LA strain acutely improved post-balloon mitral valvuloplasty (p < 0.001) and after mitral valve replacement (p = 0.012). This difference was statistically highly significant.…”
Section: Discussionmentioning
confidence: 99%
“…Atooshe Rohane et al., 2017 reported the effect of PTMC on 2D STE 1 . They recruited 46 patients undergoing either PTMC or surgical MVR irrespective of atrial rhythm abnormality—PALS significantly improved post‐intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic MS accounts for approximately 40% of the valvulopathies in the world's developing regions. According to the annual report by the WHO in 2004, 1 about 12 million people are currently affected by rheumatic fever and heart disease worldwide, and high incidence rates are reported in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation